Bullying in the workplace : an analysis of the experiences of 34 people accused of bullying - Cahill, Karen (Trinity College (Dublin, Ireland). School of Education, 2008)
This study identifies the negative effects resulting from being accused of bullying behaviour on thirty four people in their place of work. Those accused of bullying were asked to rate their accuser as a person in their own right as well as compare themselves with their accuser on a variety of aspects. Personality differences between participants in the study who were accused of bullying and a matched control group, and the coping strategies employed were sought. Possible individual and organisational antecedents to bullying were identified. In addition, to using psychometric measures to obtain quantitative data the findings were enriched by including qualitative research methods.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin